2014
DOI: 10.1530/eje-13-1044
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osteocalcin levels as a predictor of cardiovascular disease in older men and women: a population-based cohort study

Abstract: Objective: The role of osteocalcin (OC) in cardiovascular disease (CVD) is unresolved. We aimed to study the association between plasma OC concentrations and the risk of non-fatal and fatal CVDs. We also aimed to investigate whether such an association, if present, would be mediated by established metabolic risk factors. Design: A population-based longitudinal cohort study. Methods: In 1995/1996, OC was determined in blood samples drawn from 1319 subjects aged 65-88 years participating in the Longitudinal Agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Variables in the regression model included: L1‐L4 BMD, E1G AUC, and osteocalcin. Osteocalcin levels are positively associated with cardiovascular disease risk in older estrogen‐deficient women . Using this model, CBF was predicted by L1‐L4 BMD, osteocalcin, and E1G AUC (see Table ), explaining ~63% of the variance (adjusted R 2 = 0.633, F = 14.827, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Variables in the regression model included: L1‐L4 BMD, E1G AUC, and osteocalcin. Osteocalcin levels are positively associated with cardiovascular disease risk in older estrogen‐deficient women . Using this model, CBF was predicted by L1‐L4 BMD, osteocalcin, and E1G AUC (see Table ), explaining ~63% of the variance (adjusted R 2 = 0.633, F = 14.827, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a follow-up study of 1290 Korean men found that the serum osteocalcin level was not associated with the development of CVD, even after adjustment for other risk factors for CVD [29]. Another 4.1-year follow-up study also reported no association between plasma osteocalcin level and CVD in younger-old subjects (65–74 years) [13]. A positive correlation between serum osteocalcin level and atherosclerosis was found in a study of 78 patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, population-based longitudinal study by Holvik et al found that there was no association between plasma osteocalcin level and cardiovascular diseases (CVD) in younger-old subjects (65–74 years), but a higher plasma osteocalcin concentration was associated with a reduced risk of CVD in older-old men (≥75 years) while with an increased risk of CVD in older-old women (≥75 years) [13]. However, other research by Reyes-Garcia et al observed that subjects with CAD had significantly higher serum osteocalcin level than those without CAD, and that serum osteocalcin level in women was positively correlated with C-IMT [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnicity may also play a role in generating inconsistent results; among Chinese postmenopausal women, plasma phylloquinone was significantly higher and plasma ucOC was significantly lower than among British or Gambian women, while only among British women was plasma phylloquinone inversely associated with ucOC 49 . Among healthy women, serum phylloquinone and MK7, but not serum MK4, were generally inversely correlated with ucOC and the ucOC/OC ratio 67 , while there appears to be a gender difference with respect to the meaning of high plasma OC; in those aged >/=75, but not younger, higher plasma OC was associated with reduced CVD risk in men but with increased risk in women 68 .…”
Section: Bonementioning
confidence: 88%